The Role of Neutrophils as a Driver in Hepatic Ischemia-Reperfusion Injury and Cancer Growth - Kaltenmeier, Christof; Yazdani, Hamza O.; Handu, Sanah; Popp, Brandon; Geller, David; Tohme, Samer (Frontiers in Immunology, 2022)
The innate immune system plays an essential role in the response to sterile inflammation and its association with liver ischemia and reperfusion injury (IRI). Liver IRI often manifests during times of surgical stress such as cancer surgery or liver transplantation. Following the initiation of liver IRI, stressed hepatocytes release damage-associated molecular patterns (DAMPs) which promote the infiltration of innate immune cells which then initiate an inflammatory cascade and cytokine storm. Upon reperfusion, neutrophils are among the first cells that infiltrate the liver. Within the liver, neutrophils play an important role in fueling tissue damage and tumor progression by promoting the metastatic cascade through the formation of Neutrophil Extracellular Traps (NETs). NETs are composed of web-like DNA structures containing proteins that are released in response to inflammatory stimuli in the environment. Additionally, NETs can aid in mediating liver IRI, promoting tumor progression, and most recently, in mediating early graft rejection in liver transplantation. In this review we aim to summarize the current knowledge of innate immune cells, with a focus on neutrophils, and their role in mediating IRI in mouse and human diseases, including cancer and transplantation. Moreover, we will investigate the interaction of Neutrophils with varying subtypes of other cells. Furthermore, we will discuss the role and different treatment modalities in targeting Neutrophils and NETs to prevent IRI.